Prolyl Isomerase Pin1 in Human Cancer: Function, Mechanism, and Significance - Pu, Wenchen; Zheng, Yuanyuan; Peng, Yong (Frontiers in Cell and Developmental Biology, 2020)
Peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (Pin1) is an evolutionally conserved and unique enzyme that specifically catalyzes the cis-trans isomerization of phosphorylated Serine/Threonine-Proline (pSer/Thr-Pro) motif and subsequently induces the conformational change of its substrates. Mounting evidence have demonstrated that Pin1 is widely overexpressed and/or overactivated in cancer, exerting a critical influence on tumor initiation and progression via regulating the biological activity, protein degradation or nucleus-cytoplasmic distribution of its substrates. Moreover, Pin1 participates in the cancer hallmarks through activating some oncogenes and growth enhancers, or inactivating some tumor suppressors and growth inhibitors, suggesting Pin1 as an attractive target for cancer therapy. In this review, we summarize the findings on the dysregulation, mechanisms and biological functions of Pin1 in cancer cells, and also discuss the significance and potential applications of Pin1 dysregulation in human cancer.